False Gods and Libertarians: Artificial Intelligence and Community in Ahmad 'Abd al-Saläm al-Baqqäli's The Blue Flood and Heinlein's The Moon is a Harsh Mistress. - Campbell, Ian (Science Fiction Studies, 2017)
This paper examines Moroccan author Baqqali's novel al-Tufan a!-'Az.raq [The Blue Flood, 1976] from the perspective of its use of an artificial intelligence (AI) as a guiding force in a sequestered community. In the novel, the desert refuge for scientists is controlled by a massive computer. The protagonist becomes aware that the AI has become sentient and is planning to use nuclear weapons to destroy humanity. The analysis will compare The Blue Flood to Robert A. Heinlein's 1966 classic The Moon is a Harsh Mistress, wherein the AI leads the human colonists of Luna in a successful struggle for independence from Earth. In The Blue Flood a sentient being with superhuman powers can only be conceived as a form of blasphemy. From this, we can take the text as a warning to intellectuals in real-world Morocco not to dismiss Islamic and cultural traditions simply because they seem irrational. The insights gleaned from The Blue Flood open up The Moon is a Harsh Mistress to a reading that contrasts with prevailing scholarly judgment--i.e., Heinlein's novel can now be read as less a failed advocacy of libertarianism than an extended critique of the unlikelihood and vulnerabilities of a libertarian society.